2016
DOI: 10.1002/adfm.201603077
|View full text |Cite
|
Sign up to set email alerts
|

Melting of Colloidal Crystals

Abstract: 8903wileyonlinelibrary.com ClassificationCrystal melting can be categorized into two types: homogeneous melting in which the melting is equally likely to occur anywhere in the crystal, and heterogeneous melting in which the melting is more likely to occur at the surfaces and defects than the defectfree regions. Heterogeneous melting can be divided into surface melting from a free surface (i.e., the solid-vapor interface), interfacial melting from the interface of two materials (e.g., a crystal and its substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 131 publications
(233 reference statements)
2
21
0
Order By: Relevance
“…The top and bottom walls help us to form ribbonlike grain boundaries with uniform shape in the z direction, but the fluctuations in the xy plane are much weaker in a 20-layer crystal than in a monolayer crystal. This can be understood from a simple lattice-spring model [50]: A 2D square lattice has half of its springs connected in series and half connected in parallel; a two-layer square lattice has 2=5 of its springs in series and 3=5 in parallel; and a 3D cubic lattice has 1=3 of its springs in series and 2=3 in parallel. A higher fraction of springs in series corresponds to a softer structure.…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…The top and bottom walls help us to form ribbonlike grain boundaries with uniform shape in the z direction, but the fluctuations in the xy plane are much weaker in a 20-layer crystal than in a monolayer crystal. This can be understood from a simple lattice-spring model [50]: A 2D square lattice has half of its springs connected in series and half connected in parallel; a two-layer square lattice has 2=5 of its springs in series and 3=5 in parallel; and a 3D cubic lattice has 1=3 of its springs in series and 2=3 in parallel. A higher fraction of springs in series corresponds to a softer structure.…”
Section: Dimensionality Effectmentioning
confidence: 99%
“…Colloidal crystals are being actively employed as an important model system to study melting, freezing, and solid‐solid phase transitions as a function of osmotic pressure and anisotropy of interparticle interaction due to particle shape, patchiness, or dipolar interactions . The flexibility of colloidal crystals and their response to external stimuli along with their unique optical properties such as the strongly pronounced structural color and photonic band gap makes them attractive for many applications .…”
Section: Introductionmentioning
confidence: 99%
“…
dipolar interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The flexibility of colloidal crystals and their response to external stimuli [16][17][18] along with their unique optical properties such as the strongly pronounced structural color and photonic band gap makes them attractive for many applications. [19][20][21][22][23][24][25] Moreover, defects, which determine the mechanical properties of many engineering materials such as metals, [26] can be studied with "atomic" resolution using colloidal crystals.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, the limit of superheating was predicted using two different parameters based on vibrational instability and elastic shear instability, the Lindemann [1] and Born criteria [2], respectively. Even though experimental observation of the initial stage of homogeneous melting remains challenging because of the random creation of a liquid nucleus and its subsequent fast growth [5][6][7][8][9][10][11][12][13], recent developments in computer simulation have enabled us to closely examine its microscopic details [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Using molecular-dynamics (MD) simulations for a Lennard-Jones fluid, a study by Jin et al observed that homogeneous melting is initiated by clusters of vibrationally destabilised particles by satisfying the Lindemann and Born criteria [16,28].…”
Section: Introductionmentioning
confidence: 99%